Tropospheric delay efficiency from CSRS-PPP online service for meteorologists in Iran - Sam Khaniani, A.; Farzaneh, S. (Numerical Methods in Civil Engineering, 2021)
Earth’s tropospheric delay is a valuable parameter in meteorological and climatic applications and studies such as short-term weather forecasting, monitoring of severe weather conditions, and long-term climate change. One of the methods for estimating the zenith delay of the Earth’s atmosphere is the processing of the GNSS observations. In addition to estimating the station position as the main target of processing the observations, the Zenith Total Delay (ZTD) values of the signals received from the satellite are also estimated simultaneously. Processing GPS observations is complicated and costly for meteorologists other than geodesy professionals. Recently, free online GPS observation processing services have been developed. In this study, ZTD estimates of the CSRS-PPP online service in the Iranian region were evaluated to examine the potential of this data for use by meteorologists. For this purpose, 8-day observations from 46 permanent GPS stations distributed in different parts of Iran were used. Also, the ZTD values ​​obtained from the GAMIT software with differential processing method were considered as trustworthy values. In general, the tropospheric delay estimates of the CSRS-PPP service showed high agreement with the corresponding values ​​obtained from the GAMIT software. The mean correlation coefficient, RMSE, and bias of the online service estimates were 0.976, 3.38, and 0.42 mm, respectively, compared to the differential method. Based on the results of this research, it can be concluded that the ZTD products of the CSRS-PPP online service, which provide free processing for the general public, have acceptable accuracy and can be used for many studies.